EKTOPARASIT ACARINA PADA KULIT SISIK ULAR PUTIH (MICROPECIS IKAHEKA) DARI MANOKWARI - Keliopas Krey (FMIPA Universitas Papua, 2010)
Ectoparasites are species of parasites that live on the outer surface of the body of an animal. They grow and are very dependent on the life of the host. The acarina complex includes predaceous mites of infinite variation, mites associated with plants and other animals and using a variety of organic substrates as food. The result from the identification showed that acarina parasite on white snake comes from the order Parasitiformes. The acarina encountered in snake’s skin inhabit the dorsal scales in lanes or take advantage of the gaps between scales from the posterior head to the scales near the cloaca.